Photocatalytic Degradation of Orange II using Bimetallic Cu-Ni/TiO2 Photocatalysts - Riaz, Nadia; Chong, Fai Kait; Dutta, Binay Kanti; Khan, Saqib; Nurlaela, Ela (2010)

(untitled)
Photocatalytic degradation of a model azo dye, Orange II, was investigated over 10wt% bimetallic copper-nickel doped TiO2 (Degussa P-25) prepared with 9:1 Cu-Ni mass ratio. The photocatalysts were prepared via three methods: complex precipitation (CP), deposition-precipitation (DP) and wet impregnation (WI) methods. The raw photocatalysts were activated by calcination at three different temperatures (180°C, 200°C and 300°C) for 1 hour duration. Photocatalysts were characterized using Powder X-ray Diffraction (XRD) and Field-emission Scanning Electron microscopy-Energy Dispersive X-ray (FESEM- EDX). The photocatalytic degradation of Orange II was conducted at different pH under the irradiation of visible light (500 W halogen lamp). The extent of degradation for Orange II with initial concentration of 50 ppm was monitored using UV-vis spectroscopy. Results showed that complete Orange II removal was recorded at pH 6.8 for photocatalysts prepared via WI method calcined at 180°C, 200°C and 300°C. Photocatalysts prepared through DP method and calcined at 180°C, 200°C and 300°C showed 100% dye removal at pH 6.8. The extent of degradation for photocatalysts prepared via DP and CP methods was higher at pH 6.8 than pH12. On the basis of results obtained in this study, WI photocatalysts displayed the best performance compared to those prepared using CP and DP methods.